2005
DOI: 10.1073/pnas.0501145102
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic vesicle recycling studied in transgenic mice expressing synaptopHluorin

Abstract: Synaptic vesicles are recycled locally within presynaptic specializations. We examined how vesicles are reused after endocytosis, using transgenic mice expressing the genetically encoded fluorescent indicator synaptopHluorin in subsets of neurons. At both excitatory and inhibitory synapses in cultured hippocampal neurons, newly endocytosed vesicles did not preferentially enter the releasable pool of vesicles. Rather, they entered the reserve pool first and subsequently the readily releasable pool over a period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
135
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(153 citation statements)
references
References 39 publications
16
135
0
Order By: Relevance
“…As has been shown in previous studies using the thy1.2 promoter to drive transgene expression in mice (Feng et al, 2000;Li et al, 2005), we found that the pattern of spH expression varied between the different lines (Fig. 1).…”
Section: Spatial Patterns Of Transgene Expression In Sternomastoid Musupporting
confidence: 57%
See 1 more Smart Citation
“…As has been shown in previous studies using the thy1.2 promoter to drive transgene expression in mice (Feng et al, 2000;Li et al, 2005), we found that the pattern of spH expression varied between the different lines (Fig. 1).…”
Section: Spatial Patterns Of Transgene Expression In Sternomastoid Musupporting
confidence: 57%
“…To circumvent these limitations we generated transgenic lines of mice in which synaptopHluorin (spH), a pH-sensitive variant of green fluorescent protein (GFP) tethered to the vesicular membrane protein vesicle-associated membrane protein 2 (VAMP2) (Miesenbock et al 1998), is expressed in motor nerve terminals using the thy1.2 promoter (Feng et al, 2000;Li et al, 2005). This construct has been extensively used to investigate synaptic vesicle properties within hippocampal neurons in vitro Ryan, 2000, 2001;Fernandez-Alfonso et al, 2006) and at Drosophila (Poskanzer et al, 2003;Reiff et al, 2005) and mouse (Tabares et al, 2007) neuromuscular junctions in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Both ratiometric and ecliptic pHlourins have been engineered [26], although the superecliptic synaptopHluorin has been most widely employed to address important biological questions in mammalian systems. For example, synaptic vesicle recycling dynamics in neurons from Thy1-driven synaptopHluorin transgenic mice have been examined, providing results that challenged current models about constraints on vesicle reuse [27].…”
Section: Phluorins Ph-based Sensorsmentioning
confidence: 99%
“…We compared the fluorescence response of spH synapses to a stimulus of 300 APs at 10 Hz in the presence of bafilomycin with the response in the presence of dynasore. Fluorescence changes were normalized to the total pool of vesicles, which was estimated by neutralizing all vesicles with ammonium chloride (34). As shown in Fig.…”
Section: Dynasore Has No Immediate Effect On Exocytosismentioning
confidence: 99%
“…We also used the method of alkaline trapping at spH-expressing synapses (33,34) to rule out a direct effect of dynasore on exocytosis. Alkaline trapping of vesicles by bafilomycin allows for the estimation of cumulative exocytosis throughout the stimulation; endocytosed vesicles do not contribute to additional changes in fluorescence because they cannot be reacidified.…”
Section: Dynasore Has No Immediate Effect On Exocytosismentioning
confidence: 99%